2007
DOI: 10.1103/physreve.76.051918
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of essential collective motions in proteins: Theory

Abstract: A general theoretical background is introduced for characterization of conformational motions in protein molecules, and for building reduced coarse-grained models of proteins, based on the statistical analysis of their phase trajectories. Using the projection operator technique, a system of coupled generalized Langevin equations is derived for essential collective coordinates, which are generated by principal component analysis of molecular dynamic trajectories. The number of essential degrees of freedom is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
129
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(132 citation statements)
references
References 43 publications
3
129
0
Order By: Relevance
“…It also allows one to visualize them in terms of collective subunit motions (dynamic domains) and determine local conformational flexibility from a single theoretical framework. 47,48 In contrast to the conventional empirical use of principal component analysis (PCA), the present methodology relies on a robust statistical-mechanical background, 47,49 which allows for a dynamically consistent definition of protein domains, as well as a clearer description of the local bond flexibility within the same theoretical framework. Using this technique, the essential collective coordinates of a protein can be determined via PCA using small portions of standard MD trajectories thereby providing a characterization of stable structural properties that persist over a longer period (Potapov et al, submitted).…”
Section: Comparative Analysis Of Essential Collective Dynamics and Nmmentioning
confidence: 99%
See 2 more Smart Citations
“…It also allows one to visualize them in terms of collective subunit motions (dynamic domains) and determine local conformational flexibility from a single theoretical framework. 47,48 In contrast to the conventional empirical use of principal component analysis (PCA), the present methodology relies on a robust statistical-mechanical background, 47,49 which allows for a dynamically consistent definition of protein domains, as well as a clearer description of the local bond flexibility within the same theoretical framework. Using this technique, the essential collective coordinates of a protein can be determined via PCA using small portions of standard MD trajectories thereby providing a characterization of stable structural properties that persist over a longer period (Potapov et al, submitted).…”
Section: Comparative Analysis Of Essential Collective Dynamics and Nmmentioning
confidence: 99%
“…[43][44][45] Recently, a novel theoretical formalism has been developed in our group to analyze collective coarse-grained dynamics in proteins. 47 This approach allows one to readily identify long term collective motions in a large molecule. It also allows one to visualize them in terms of collective subunit motions (dynamic domains) and determine local conformational flexibility from a single theoretical framework.…”
Section: Comparative Analysis Of Essential Collective Dynamics and Nmmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty arises from two factors: ͑1͒ the intrinsic dimensionality for most problems is unknown, and ͑2͒ there is debate for some problems as to whether simulation approaches can provide sufficient sampling of the phase space to facilitate an accurate analysis of dimensionality reduction. 3,13,24,25,27,42 In this paper, we investigate the ability of well-known nonlinear dimensionality reduction algorithms to identify accurate, low-dimensional substructures in the conformation space for an eight-membered ring. We chose this particular molecule for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…3,12,18,19 In addition to providing reduced complexity, an accurate representation for correlated molecular motions can aid in the interpretation of NMR and x-ray studies. [20][21][22][23][24][25][26] It has been shown that dimensionality reduction can be used to extend the time scales of MD, and a theoretical framework for low-dimensional simulation with Langevin MD or metadynamics is a topic of current investigation. 25,27,28 In addition to improving the efficiency of simulation, a logical extension is to utilize lowdimensional surrogate spaces for problems in optimization that occur in molecular recognition and self-assembly.…”
Section: Introductionmentioning
confidence: 99%